The 1st International Electronic Conference on Food Science and Functional Foods 2020
DOI: 10.3390/foods_2020-07716
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Antimicrobial Actions of Greek Honeys from the Island of Lemnos and Manuka Honey from New Zealand against Clinically Important Bacteria

Abstract: Honey is a natural food that has a long history as a traditional medicine because of its many biological characteristics, including antimicrobial, antioxidant, anti-tumor and anti-inflammatory properties. In this study, the antimicrobial actions of eight different honeys from Lemnos island (north-eastern Greece) plus manuka honey (from New Zealand, UMF 30+, licensed in many countries as topical medical preparation) were evaluated against ten clinically relevant bacteria, including five Gram-positive (Staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The pH of honey is between 3.2 and 4.5 [26,27,38,70]. This acidity is low enough to inhibit the growth of most microorganisms of the ones tested here [26,27,38,[70][71][72]. Although statistically significant differences were observed among the pH values off the different honey types, it was not possible to conclude any positive (or negative) statistically significant effect of these differences on the antimicrobial action either in well diffusion experiments or in MIC estimates.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The pH of honey is between 3.2 and 4.5 [26,27,38,70]. This acidity is low enough to inhibit the growth of most microorganisms of the ones tested here [26,27,38,[70][71][72]. Although statistically significant differences were observed among the pH values off the different honey types, it was not possible to conclude any positive (or negative) statistically significant effect of these differences on the antimicrobial action either in well diffusion experiments or in MIC estimates.…”
Section: Discussionmentioning
confidence: 82%
“…The second antimicrobial reason of honey is the pH values. The pH of honey is between 3.2 and 4.5 [26,27,38,70]. This acidity is low enough to inhibit the growth of most microorganisms of the ones tested here [26,27,38,[70][71][72].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The study concluded that environmental conditions, flower species and geographical location of flower sources are responsible for the variability in the antimicrobial activity of honey. Gkoutzouvelidou et al, (2021) investigated an inquiry encompassing eight honey samples sourced from Lemnos Island, in addition to one Manuka honey sample. The objective was to assess their antimicrobial potential against Listeria monocytogenes bacteria.…”
Section: Antimicrobial Effects Of Honey On Listeria Monocytogenesmentioning
confidence: 99%